Are People Enrolled in NCMS and CURBMI Susceptible in Catastrophic Health Expenditure? Evidence From China. (May 2020) - Xu, Xinpeng; Gu, Hai; You, Hua; Bai, Lan; Li, Decheng; Cui, Nan; Wu, Wenxuan; Kou, Yun
This study investigated associations between different types of medical insurance and the incidence of catastrophic health expenditure among middle-aged and the aged in China. The data came from the China Health and Retirement Longitudinal Survey implemented in 2013, with 9782 individuals analyzed. Probit regression models and multiple linear regressions were employed to explore the relationship mentioned above and potential mechanisms behind it. It was found that compared with participants in Urban Resident Basic Medical Insurance, individuals participating in New Cooperative Medical Scheme and Coordinating Urban and Rural Basic Medical Insurance was less likely to undergo catastrophic health expenditure ( P < .001, P = .008), especially for low-income and middle-income group. Participants in New Cooperative Medical Scheme and Coordinating Urban and Rural Basic Medical Insurance were more likely to utilize inpatient medical service ( P < .001, P = .020) and choose low-level medical institutions for treatment ( P = .003, P = .006). And individuals participating in New Cooperative Medical Scheme had lower out-of-pocket expenditure ( P = .034). The study showed the significant difference in the incidence of catastrophic health expenditure among participants in different medical insurances. Efforts should be made to improve the service quality of grassroots medical institutions except for the increase of reimbursement ratio, so that rural residents can enjoy high-quality medical services.